Cadherin Signaling in Cancer: Its Functions and Role as a Therapeutic Target - Yu, Weina; Yang, Li; Li, Ting; Zhang, Yi (Frontiers in Oncology, 2019)
Abstract: Cadherins are members of a large family of transmembrane glycoproteins that mediate calcium-dependent homotypic cell-cell adhesion. Cadherin-mediated adhesion regulates cell growth and differentiation throughout life. Through the establishment of the cadherin-catenin complex, cadherins provide normal cell-cell adhesion and maintain homeostatic tissue architecture. Because of the importance of cadherins in cell recognition, adhesion, and signaling, disruption of cadherin function has significant implications for the development and behavior of tumors. Altered cadherin expression plays a vital role in tumorigenesis, tumor progression, angiogenesis and tumor immune response. Based on ongoing research into the role of cadherin signaling in malignant tumors, cadherins are now being considered as potential targets for cancer therapies. This review will demonstrate the mechanisms of cadherin involvement in tumor progression, and consider the clinical significance of cadherins as therapeutic targets.